2021
DOI: 10.1371/journal.pone.0253209
|View full text |Cite
|
Sign up to set email alerts
|

Accurate extraction of surface water in complex environment based on Google Earth Engine and Sentinel-2

Abstract: To realize the accurate extraction of surface water in complex environment, this study takes Sri Lanka as the study area owing to the complex geography and various types of water bodies. Based on Google Earth engine and Sentinel-2 images, an automatic water extraction model in complex environment(AWECE) was developed. The accuracy of water extraction by AWECE, NDWI, MNDWI and the revised version of multi-spectral water index (MuWI-R) models was evaluated from visual interpretation and quantitative analysis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…However, the models often misclassify soil, rock, clouds, ice, and shadow as water and often rely on cloud-free, optical RS imagery, which is not always available. The authors in [157] used masking, filtering, and segmentation algorithms to identify bodies of water in Sri Lanka in complex, mountainous environments. It is challenging to repeatedly produce up-to-date, accurate surface water maps over large areas.…”
Section: Water Mapping and Water Quality Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the models often misclassify soil, rock, clouds, ice, and shadow as water and often rely on cloud-free, optical RS imagery, which is not always available. The authors in [157] used masking, filtering, and segmentation algorithms to identify bodies of water in Sri Lanka in complex, mountainous environments. It is challenging to repeatedly produce up-to-date, accurate surface water maps over large areas.…”
Section: Water Mapping and Water Quality Monitoringmentioning
confidence: 99%
“…The authors designed the network to work with many different satellite platforms as long as they have a set group of input bands. The authors in [157] used masking, filtering, and segmentation algorithms to identify bodies of water in Sri Lanka in complex, mountainous environments. They showed that their model performs well even in the presence of shadow or soil and does so much better than other common index-based methods like NDWI, MNDWI, or multi-spectral water index (MuWI-R).…”
Section: Abbreviationsmentioning
confidence: 99%
“…Other research papers have adapted the GEE for water body extraction using a variety of satellite sensors and delivery methods. The most recent papers have leveraged the GEE to process both multi-spectral Sentinel-2 (S-2), Landsat-8 and synthetic aperture radar (SAR) Sentinel-1 (S-1) images using deep learning (DL) frameworks [29][30][31]; similar data sources of satellite sensors, histogram based, machine learning (ML), and clustering (i.e., K-Means) classifications have been implemented [32][33][34] to derive a scalable water map. ML and DL coupled with the GEE has the potential to derive high quality maps of water distribution, despite the implementation of the model being very complex in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Multispectral images have numerous bands, ranging from visible to infrared light, and their extensive spectral information allows for reliable object identification. As a result, multispectral change detection has found widespread application in the fields of environmental monitoring [1][2][3][4], resource inquiry [5][6][7], urban planning [8][9][10], and natural catastrophe assessment [11][12][13].…”
Section: Introductionmentioning
confidence: 99%